Herbicide options for weed control in herbicide resistant canola cultivars with particular reference to glufosinate ammonium - Molefe, Bontleng Petronella (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.